Differences in planning performance, a neurocognitive endophenotype, are associated with a functional variant in PER3 gene (2015)
Performance alterations in executive function have been studied as potential endophenotypes for several neuropsychiatric diseases. Planning is an important component of executive function and has been shown to be affected in diseases such as attention deficit hyperactivity disorder, schizophrenia, obsessive–compulsive disorder and Parkinson’s disease. Several genes related to dopaminergic systems, such as COMT, have been explored as candidates for influencing planning performance. The circadian clock gene PERIOD3 (PER3) has been shown to be associated with several complex behaviors in humans and could be involved in different signaling mechanisms. In this study, we evaluated the possible association between a functional polymorphism in the PER3 gene (PER3-VNTR, rs57875989) and performance in a commonly used test of planning (Tower of London, TOL) in 229 healthy subjects from Bogotá, Colombia. PER3-VNTR genotyping was carried out with conventional PCR and all participants completed the TOL test using the computerized Psychology Experiment Building Language (PEBL) battery. A linear regression model was used for the analysis of association with the SNPStats program. We found that 4/4 genotype carriers showed a better performance and made fewer moves, in comparison to 4/5 and 5/5 genotype carriers (p?=?0.003). These results appear to be independent from effects of this polymorphism on self-reported average hours of sleep during work days in our sample.